Seasonal abundance of commercially important finfish and shellfish seed resources in Shambhavi Estuary, Karnataka - Purushottama, G. B.; Dineshbabu, A. P.; Saravanan, R.; Syda Rao, G. (Indian Journal of Fisheries, 2014)
Year round availability of commercially important fin and shellfish seed is one of the essential requirements for capture based aquaculture (CBA). The present study was undertaken to ascertain the availability of finfish and shellfish seed resources in the Shambhavi Estuary, Mulki, Karnataka. Six species of commercially important seed resources were recorded viz., Mugil spp., Etroplus suratensis, Lutjanus argentimaculatus, Lutjanus russelli, Fenneropenaeus indicus and Penaeus monodon. The distribution and relative abundance of the above seeds were studied in different seasons for a period of 12 months from March, 2011 to February, 2012 in relation with the important environmental parameters such as rainfall, temperature, dissolved oxygen, salinity and pH. All the above parameters studied showed significant variation with the seasonal abundance of the fish and shellfish seeds. Among the finfish seeds, Mugil spp. and E. suratensis dominated and contributed to 56.4% and 25.6% respectively in the month of June. However, these two species were available in small quantities during rest of the study period. The occurance of P. argentimaculatus and L. russelli was to the tune of 1.5% (November) and 3.2% (May) respectively. Among shrimp seeds, F. indicus showed distinct seasonal variation with their peak abundance in the early pre-mansoon (January/February) months and late post-mansoon months (November/ January). Whereas, P. monodon was predominant during early post-monsoon season (November/December). The outcome of this study would be useful for planning of capture based-aquaculture of commercially important finfish and shellfish species in coastal Karnataka.